The Controversy, Challenges, and Potential Benefits of Putative Female Germline Stem Cells Research in Mammals - Zezheng Pan; Mengli Sun; Xia Liang; Jia Li; Fangyue Zhou; Zhisheng Zhong; Yuehui Zheng (Stem Cells International)
The conventional view is that female mammals lose their ability to generate new germ cells after birth. However, in recent years, researchers have successfully isolated and cultured a type of germ cell from postnatal ovaries in a variety of mammalian species that have the abilities of self-proliferation and differentiation into oocytes, and this finding indicates that putative germline stem cells maybe exist in the postnatal mammalian ovaries. Herein, we review the research history and discovery of putative female germline stem cells, the concept that putative germline stem cells exist in the postnatal mammalian ovary, and the research progress, challenge, and application of putative germline stem cells in recent years.